White Emitting ZnS Nanocrystals： Synthesis and Spectrum Characterization - 黄青松 董冬青 徐建萍 张晓松 张宏敏 李岚 (Chinese physics letters, 2010)
Spherical organic-bonded ZnS nanocrystals with 4.0 4-0.2 nm in diameter are synthesized by a liquid-solid-solution method. The photoluminescence spectrum of sample （[S^2-]/[Zn^2＋] = 1.0） shows a strong white emission with a peak at 490nm and - 170 nm full widths at half maximum. By Gauss fitting, the white emission is attributed to the overlap of a blue emission and a green-yellow emission, originating from electronic transitions from internal S^2- vacancies level to valence band and to the internal Zn^2＋ vacancy level, respectively. After sealingZnS nanocrystals onto InGaN chips, the device shows CIE coordinates of （0.29,0.30）, which indicates their potential applications for white light emitting diodes.